2020
DOI: 10.3390/pharmaceutics12111094
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Consumption Challenges Hepatic Mitochondrial Bioenergetics and Elicits Transcriptomics Reprogramming in Healthy Wistar Rats

Abstract: An emergent trend of blueberries’ (BB) “prophylactic” consumption, due to their phytochemicals’ richness and well-known health-promoting claims, is widely scaled-up. However, the benefits arising from BB indiscriminate intake remains puzzling based on incongruent preclinical and human data. To provide a more in-depth elucidation and support towards a healthier and safer consumption, we conducted a translation-minded experimental study in healthy Wistar rats that consumed BB in a juice form (25 g/kg body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 146 publications
1
16
0
Order By: Relevance
“…Moreover, other studies showed an antioxidant effect of bilberry leaves extract in serum of male Wistar rats under a double challenge composed of HFD and STZ [ 93 ]. Likewise, in a recent study from our group, long-term supplementation of BB juice boosted serum antioxidant activity in a healthy Wistar rats [ 130 ]. Nevertheless, there has been some controversy on BB-derived polyphenols benefits on total antioxidant activity in both in vivo and human studies [ 131 , 132 , 133 , 134 , 135 ].…”
Section: Blueberries Beneficial Outcomes In (Pre)diabetes Progression—a Multi-modal Functional Fruitmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, other studies showed an antioxidant effect of bilberry leaves extract in serum of male Wistar rats under a double challenge composed of HFD and STZ [ 93 ]. Likewise, in a recent study from our group, long-term supplementation of BB juice boosted serum antioxidant activity in a healthy Wistar rats [ 130 ]. Nevertheless, there has been some controversy on BB-derived polyphenols benefits on total antioxidant activity in both in vivo and human studies [ 131 , 132 , 133 , 134 , 135 ].…”
Section: Blueberries Beneficial Outcomes In (Pre)diabetes Progression—a Multi-modal Functional Fruitmentioning
confidence: 88%
“…In fact, this polyphenol has a positive impact on mitochondrial biogenesis related with an increased mRNA expression of PGC-1α and SIRT1 along with higher contents of mtDNA and cytochrome c [ 150 ]. Remarkably, recent data from our group revealed that long-term BB fruits intake in a juice form elicited an accentuated bioenergetic remodeling in isolated hepatic mitochondria along with a metabolic transcriptional adaptive response in healthy animals [ 130 ]. Further animal research also showed that the attenuation of hepatic steatosis and enhancement of lipolysis following exposure of hepatic cells to BB polyphenols can be promoted by modulation of autophagy [ 36 ].…”
Section: Blueberries Beneficial Outcomes In (Pre)diabetes Progression—a Multi-modal Functional Fruitmentioning
confidence: 99%
“…BBs juice (BJ) was obtained as described in a previous study [38]. Briefly, BBs were weighed, blended with sucrose solution (35%), and converted into juice to assure consumption of whole fruit parts (peel, pulp, and seeds).…”
Section: Blueberry Juice Preparationmentioning
confidence: 99%
“…The volume of sucrose solution added was corrected every day to guarantee that 25 g/kg of BW of BBs were daily consumed by the animals. This BBs dose was selected based on a previous study of our group [38].…”
Section: Blueberry Juice Preparationmentioning
confidence: 99%
See 1 more Smart Citation